1995
DOI: 10.1159/000203992
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Erythropoietin in Patients with Acquired Aplastic Anaemia

Abstract: The plasma erythropoietin (Epo) concentration was measured by radioimmunoassay in 75 patients with acquired aplastic anaemia. Overall there was an inverse relationship between the concentration of plasma Epo and the degree of anaemia. Plasma Epo concentrations were lower in patients who were sampled soon after diagnosis as opposed to those studied at later times. Although a decrease in the plasma Epo concentration was noted in all erythroid respond-ers following immunosuppressive (IS) therapy or bone marrow tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…9a ). The Epo-concentration range affecting cell size, from 0.01 to 10 Units/ml, corresponds to the entirety of the physiological and stress range in vivo 57 , 58 . Higher Epo also increased reticulocyte size heterogeneity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9a ). The Epo-concentration range affecting cell size, from 0.01 to 10 Units/ml, corresponds to the entirety of the physiological and stress range in vivo 57 , 58 . Higher Epo also increased reticulocyte size heterogeneity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that cell size was increased in an Epo-concentrationdependent manner, with larger cells at every stage of differentiation, including reticulocytes (Fig 6b, Extended Data Fig 8a). The Epo concentration range affecting cell size, from 0.01 to 10 Units/ml, covers the entirety of the physiological and stress range that is found for Epo in vivo 66,67 . In addition to increasing reticulocyte diameter, higher Epo concentration also increased reticulocyte size distribution, as shown by respective coefficients of variation of the diameters, making them more heterogeneous (Extended Data Fig 8b).…”
Section: Epo Increases Cell Size and Prolongs Erythroid Maturation Ovmentioning
confidence: 96%